Public Communication of the DPRD in the Implementation of Community Welfare Programs in Bulukumba Regency - Asdar Asdar; Suprianto Suprianto; M Awaluddin; Muhammad Luthfi Siraj; Umar Iskandar (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Public communication is an important element in governance because it affects public participation, policy legitimacy, and public accountability. However, the study of DPRD public communication in the entire cycle of implementing community welfare programs is still relatively limited. This study aims to analyze the public communication of the Bulukumba Regency DPRD at the planning, implementation, and reporting and evaluation stages of community welfare programs. The research uses a qualitative approach with a descriptive method. Data was obtained through in-depth interviews, observations, and documentation involving leaders and members of the DPRD, legislative bodies, related commissions, and other stakeholders. Data analysis uses the interactive model Miles, Huberman, and Saldaña which includes data condensation, data presentation, and conclusion drawn. The results of the study show that at the planning stage, public communication is carried out through recess, hearings, working visits, and public consultations that allow people's aspirations to be accommodated in regional policies, including Regional Regulation Number 1 of 2016 concerning CSR. At the implementation stage, public communication functions as a means of coordination and supervision between the DPRD, local governments, OPDs, and the community. Meanwhile, at the reporting and evaluation stage, public communication is realized through the discussion of the APBD accountability report, evaluation of budget realization, and follow-up on audit results. This study concludes that DPRD public communication plays a role as a mechanism for absorbing aspirations, coordination, supervision, and accountability in realizing responsive, participatory, and accountable community welfare programs.